Delay analysis in construction contracts - Keane, P. J.; Caletka, A. F. (Chichester, West Sussex, United Kingdom : Hoboken, NJ : John Wiley and Sons, Inc., 2015)
The most significant unanticipated costs on many construction projects are the financial impacts associated with delay and disruption to the works. Assessing these, and establishing a causal link from each delay event to its effect, contractual liability and the damages experienced as a direct result of each event, can be difficult and complex.
Includes bibliographical references and index.
oif 21/01/2020
Loans
Keywords: Construction industry--Planning; Construction industry--Cost control; Production scheduling; Construction contracts.--Costs; Penalties, Contractual